Analisis Peramalan Permintaan Jahe Merah Bubuk Dengan Metode Moving Average dan Exponential Smoothing Pada PT. Natrindo Surya Prima - Wisnianingsih, Nova; Nurrokhman, Agus (Jurnal Optimalisasi, 2024)
A common problem faced by companies is how to predict future production of goods based on previously collected data. Companies only produce according to orders, so that companies carry out the production process only according to the amount requested by consumers. When there is excess, this excess is stored in stock, this is to meet sudden consumer demand. Forecasts greatly influence management decisions to determine the amount of production of goods to be supplied by the company, general business and economic conditions, competitor reactions and actions, government actions, market trends, product life cycles, styles and fashions, changes in demand and innovation in consumer technology. This study aims to identify and analyze the results of forecasting red ginger powder production using the moving average forecasting method and exponential forecasting. This method has the advantage of greatly reducing data storage problems, so there is no need to store all historical data. This method is also simple and transparent which is widely used in various organizational activities such as inventory management, scheduling, and revenue management. For forecasting, the more data used for forecasting, the more accurate the forecasting results. The results of this study have succeeded in creating a forecasting system for the production of red ginger powder at PT Natrindo Surya Prima, namely using exponential smoothing forecasting with a value of α = 1. So it is easier to determine the amount of red ginger powder production in the following years.